Marketing Strategy for Chinese Market to Increase Room Occupancies at The Plataran Ubud Hotel - I Ketut Muliadiasa; Ni Putu Isha Aprinica (Institut Pariwisata dan Bisnis Internasional, 2021)
Nowadays, Chinese tourists dominate Indonesian tourism, an increase in the number of Chinese tourists visiting Bali is quite significant every year. The marketing method that focuses on the Chinese market is still not maximized. This is evidenced by a decrease in the number of Chinese tourists visits. Even now the room occupancy rate targeted by Plataran Hotel Ubud has not yet reached the desired target. The urgency of this research is a degradation in the volume of sales of rooms at Hotel Plataran Ubud, which causes a derivation in the quantity of tourist visits which results in a decrease in employment for the community. Data collection techniques used were observation, interviews, document studies and questionnaires. The data analysis technique is using qualitative descriptive analysis, IFAS EFAS and SWOT analysis. The results of this study are to produce the right marketing strategy used in increasing the sales volume of hotel rooms at the Ubud Plataran Hotel.